Iqbal and modern Islamic educationists part 2: the perceived objectives of education and practices on the ground – a comparative analysis - Ali, Muhammad Abid; Hussien, Suhailah (Institute of Business Management, 2021)
Nations design their education systems to prepare youth for achieving national goals and objectives as perceived by that nation. The education system reflects nations’ epistemological, ontological and axiological assumptions. Accordingly, the secular west has designed its educational intervention based on their assumptions and is diametrically opposite to Islamic belief and culture (Asad, 2005). Our contemporary education system is largely developed by the west on secular assumptions of life and as such is leading our children to develop the Western secular perceptual framework. Iqbal explicates that a dynamic education system based on Islamic percepts is a prerequisite for developing an Islamic individual as well as an effective Islamic ummah. The first part of this research article, Iqbal and modern Islamic educationists, part 1: Perceived Aims and Objectives of education – a comparative analysis, focused on the comparative analysis of aims and objectives of education from an Islamic perspective as perceived by Islamic educationists in Pakistan with that of Iqbal’s, as drawn from his two Persian anthologies of Asrar I khudi (Secrets of the Self), and Ramooz I bikhudi (Mysteries of Selflessness). In the second part, the practices or modus operandi of these Islamic educationists to achieve their perceived aims and objectives of education from an Islamic perspective have been analyzed in the light of Iqbal’s educational philosophy. The findings show that though to some extent the aims and objectives comply with Iqbal’s prescribed aims and objectives of education, but on the ground, the practices which the Islamic educators have adopted, largely from the western 8approach of education, act as inhibitors to the spirit of those aims and this is not being realized by these educators.